EXERCISE MYOPATHY: CHANGES IN MYOFIBRILS OF FAST-TWITCH MUSCLE FIBRES - Kaasik, P.; Umnova, M.; Seene, T. (Biology of Sport, 2014)
The purpose of the present study was to determine the relationships between the changes of myofibrils in fast-twitch oxidative-glycolytic (type IIA) fibres and fast-twitch glycolytic (type IIB) muscle fibres, protein synthesis and degradation rate in exercise-induced myopathic skeletal muscle. Exhaustive exercise was used to induce myopathy in Wistar rats. Intensity of glycogenolysis in muscle fibres during exercise, protein synthesis rate, degradation rate and structural changes of myofibrils were measured using morphological and biochemical methods. Myofibril cross sectional area (CSA) in type IIA fibres decreased 33% and type IIB fibres 44%. Protein degradation rate increased in both type IIA and IIB fibres, 63% and 69% respectively in comparison with the control group. According to the intensity of glycogenolysis, fast oxidative-glycolytic fibres are recruited more frequently during overtraining. Myofibrils in both types of fast-twitch myopathic muscle fibres are significantly thinner as the result of more intensive protein degradation. Regeneration capacity according to the presence of satellite cells is higher in type IIA fibres than in type IIB fibres in myopathic muscle.